Novel CUL3 Variant Causing Familial Hyperkalemic Hypertension Impairs Regulation and Function of Ubiquitin Ligase Activity. Issue 1 (2nd December 2021) - Chatrathi, Harish E.; Collins, Jason C.; Wolfe, Lynne A.; Markello, Thomas C.; Adams, David R.; Gahl, William A.; Werner, Achim; Sharma, Prashant
Abstract : Supplemental Digital Content is available in the text. Abstract : Familial hyperkalemic hypertension is caused by pathogenic variants in genes of the CUL3 (cullin-3)-KLHL3 (kelch-like-family-member-3)-WNK (with no-lysine [K] kinase) pathway, manifesting clinically as hyperkalemia, metabolic acidosis, and high systolic blood pressure. The ubiquitin E3 ligase CUL3-KLHL3 targets WNK kinases for degradation to limit activation of the thiazide-sensitive NCC (Na-Cl cotransporter). All known variants in CUL3 lead to exon 9 skipping (CUL3Δ9) and typically result in severe familial hyperkalemic hypertension and growth disturbances in patients. Whether other variants in CUL3 cause familial hyperkalemic hypertension is unknown. Here, we identify a novel de novo heterozygous CUL3 variant (CUL3Δ474–477) in a pediatric familial hyperkalemic hypertension patient with multiple congenital anomalies and reveal molecular mechanisms by which CUL3Δ474–477 leads to dysregulation of the CUL3-KLHL3-WNK signaling axis. Using patient-derived urinary extracellular vesicles and dermal fibroblasts, in vitro assays, and cultured kidney cells, we demonstrate that CUL3Δ474–477 causes reduced total CUL3 levels due to increased autoubiquitination. The CUL3Δ474–477 that escapes autodegradation shows enhanced modification with NEDD8 (neural precursor cell expressed developmentally down-regulated protein 8) and increased formation of CUL3-KLHL3 complexes that are impaired in ubiquitinating WNK4. Proteomic analysis of CUL3 complexes revealed that, in addition to increased KLHL3 binding, the CUL3Δ474–477 variant also exhibits increased interactions with other BTB (Bric-a-brac, Tramtrack, and Broad complex) substrate adaptors, providing a rationale for the patient's diverse phenotypes. We conclude that the pathophysiological effects of CUL3Δ474–477 are caused by reduced CUL3 levels and formation of catalytically impaired CUL3 ligase complexes.